Dependência espacial do crescimento econômico nos estados brasileiros - Feitosa, Carlos Fábio Damasceno (2023)
Economic growth, both in Brazil and in the world, does not occur linearly across regions. However, regions and localities can take advantage of the growth of neighboring or close places. Several studies analyze the dynamics of economic growth from a temporal perspective, such as economic cycles, but recently several studies have focused on this relationship in a spatial way. Thus, in this dissertation, we study whether there is a spatial dependence of economic growth among Brazilian states. To achieve this objective, a spatial autorregressive and moving average (SARMA) was used with economic growth data from the 27 Brazilian states between 1989 and 2019. Since the 2000s, there was greater integration between the states, driven by the growth of the economy. Through Morgan statistics, an increase in spatial dependence between Brazilian states between 2000 and 2010 was verified, which indicates greater integration leveraged by greater economic growth. As of 2010, however, this dependency is reduced due to international factors and internal fiscal problems.